You can't spell America without me : the really tremendous inside story of my fantastic first year as president, Donald J. Trump - Baldwin, Alec, 1958-; Andersen, Kurt, 1954- (Penguin Press, 2017)
A satirical memoir written in the style of Donald Trump shares lampooning insights into the forty-fifth president's election, disdain for the press, backroom strategy sessions with White House advisers, and world-changing decisions.